Strategi Pemerintah Daerah Provinsi Papua Barat Dalam Meningkatkan Kontribusi Pendapatan Asli Daerah Terhadap Anggaran Pendapatan Dan Belanja Daerah Periode 2016-2020 - Homer , Mersi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research study aims to detail the strengths and strategies of the West Papua Provincial Government. The Independence Ratio Analysis used is the analysis used in the implementation of this research. While the SWOT analysis in this study is to develop the best. The results of this study indicate that Financial Independence sourced from the Regional Original Income of West Papua Province is in the very low category. The problems include the limited ASN resources in public services, inadequate facilities and infrastructure, insufficient multiplication of capabilities from local revenue owned; development of an inefficient regional financial management information system